2008
DOI: 10.1158/1078-0432.ccr-08-1113
|View full text |Cite
|
Sign up to set email alerts
|

Nonpegylated Liposomal Doxorubicin (TLC-D99), Paclitaxel, and Trastuzumab in HER-2-Overexpressing Breast Cancer: A Multicenter Phase I/II Study

Abstract: on behalf of the Spanish Breast Cancer Cooperative Group SOLTI Abstract Purpose: To determine the recommended dose, cardiac safety, and antitumor activity of nonpegylated liposomal doxorubicin (TLC-D99), paclitaxel, and the anti-HER-2 monoclonal antibody trastuzumab in patients with HER-2-overexpressing locally advanced nonoperable breast cancer (LABC) and metastatic breast cancer (MBC). Experimental Design: Women with measurable, previously untreated, HER-2-overexpressing LABC and MBC with a baseline left ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…The data reported by Stickeler et al find support in other small trials in which either pegylated [19][20][21] or nonpegylated doxorubicin [22] was combined with trastuzumab. Of note, in a Phase I/II trial that built on the combination of doxorubicin, paclitaxel and trastuzumab of the NOAH study and substituted the naked anthracycline with the non-pegylated liposomal formulation TLC-D99 the Authors reported an outstanding objective response rate of 98.1% in 69 patients with HER2-positive metastatic breast cancer, and a median time to progression exceeding 22 months at the cost of very good cardiac tolerability [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The data reported by Stickeler et al find support in other small trials in which either pegylated [19][20][21] or nonpegylated doxorubicin [22] was combined with trastuzumab. Of note, in a Phase I/II trial that built on the combination of doxorubicin, paclitaxel and trastuzumab of the NOAH study and substituted the naked anthracycline with the non-pegylated liposomal formulation TLC-D99 the Authors reported an outstanding objective response rate of 98.1% in 69 patients with HER2-positive metastatic breast cancer, and a median time to progression exceeding 22 months at the cost of very good cardiac tolerability [23].…”
mentioning
confidence: 99%
“…The clinical results are so promising to justify renewed attention to the possibility of widening the indication of trastuzumab to also include the co-administration with anthracyclines. Such scenario will have to wait for the results of prospective randomized tests that in some cases are already ongoing, as in the Breast cancer Adjuvant Caelyx Herceptin (BACH) study [8], or in the announced trial that will prospectively test in women with metastatic breast cancer the combination of trastuzumab and paclitaxel verses TLC-D99, trastuzumab and paclitaxel [23]. The time for reconsidering the taboo of never combining trastuzumab with anthracyclines has come.…”
mentioning
confidence: 99%
“…Echocardiography has been used to determine cardiac function before treatment with NPLD [29,40]. BNP as marker for cardiac dysfunction could be used for therapeutic monitoring [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…112 Moreover, most of the trials associating liposomal anthracyclines with trastuzumab in metastatic disease revealed low incidence of symptomatic cardiac events. 50,[53][54][55][56][57] The CREC also reviewed a number of trastuzumab monotherapy trials and found a 3%-7% range of cardiac dysfunction. Patients enrolled in these trials were largely unselected and many of the patients who developed cardiac dysfunction had underlying cardiac disease or had received a cumulative anthracycline dose .400 mg/m.…”
Section: Cardiac Toxicity In Metastatic Breast Cancermentioning
confidence: 99%